Fostering Young Muslims’ Digital Entrepreneurship through Computer Technician Education - Nurhayati, Sri; Susanto, Sadi (JIE (Journal of Islamic Education), 2024)
As the digital economy grows, there is an urgent need for Muslim youth to develop technical and entrepreneurial skills. This study aims to analyze the implementation and outcomes of a computer technician entrepreneurship education program in improving the digital entrepreneurship competency of Muslim youth. This study uses a qualitative case study approach with data collection techniques in the form of interviews, observations, and document analysis. Data analysis with thematic analysis includes data recognition, coding, and conclusions. The results show that the program curriculum, aligned with the Indonesian National Qualifications Framework (INQF), successfully combines technical training in computer hardware and software with entrepreneurship education. Participants in the Digital Entrepreneurship Education program reported significant improvements in technical skills, especially in problem-solving and digital business management, and the development of managerial competencies such as financial management and online marketing. The practice-based learning method, complemented by Islamic guidance and values, fosters entrepreneurial readiness and helps program participants navigate ethically in the digital economy. This method is very beneficial for Muslim youth because it is in accordance with the experiential learning approach recommended in Islamic education, which emphasizes practice and reflection. In addition, the guidance provided focuses on technical advice and moral and ethical support, which is essential for their personal and professional development. Some areas that need improvement include upgraded facilities and more comprehensive mentoring support. This study offers important insights for policymakers and educators, highlighting the implementation of digital entrepreneurship education programs that combine technical training with entrepreneurship education to shape Muslim youth into ethical and competent digital entrepreneurs.